The experience of activity pacing in chronic pain management-An interpretive phenomenological analysis of out-patient physiotherapists and patients - Scott-Dempster, C; Toye, F; Barker, K (Taylor and Francis, 2017)
Purpose: Activity pacing (AP) is widely used to manage chronic pain. However, recent developments in pain management do not necessarily include AP. Research has explored the experience of AP for physiotherapists who specialize in chronic pain. The innovation of this study is to build on previous research by exploring the experiences of patients and physiotherapists who do not specialize in chronic pain. Methods: We interviewed eight patients with chronic musculoskeletal pain who had used AP and eight physiotherapists working in an out-patient department who had not specialized in chronic pain. Interviews were recorded, and transcribed verbatim and Interpretative Phenomenological Analysis (IPA) were used for analysis. Results: We present the following themes: 1) I have tried everything and have no other place to go; 2) AP provides a tangible, physical structure that can be used flexibly; 3) working to retune the brain to a different way of life; 4) retuning the brain can pay off in the end as “less is more”; 5) working hard to connect with patients; 6) connecting with patients can be exhausting; and 7) the patient needs to be on board. Conclusion: AP can provide a useful vehicle for psychological change through experiential learning. It can support psychological flexibility and is not incompatible with other biopsychosocial approaches.